2007
DOI: 10.1002/asna.200610751
|View full text |Cite
|
Sign up to set email alerts
|

The inner structure of the S0 galaxy NGC 3384

Abstract: We re-investigate the lenticular galaxy NGC 3384, a member of the Leo I galaxy group, using HST and multi-colour Calar Alto observations. Various approaches are used to visualize the two known peculiar components, the so-called inner component (IC) and the elongated component (EC), on the HST images. The methods were checked in detail using synthetical images from simulated galaxies. For the first time, we make the IC as well as the inner part of the EC visible on direct images. The results confirm both the ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…1), and NGC 3384 (Busarello et al 1996, their Fig. 7;Cappellari & Emsellem 2004;Erwin 2004;Meusinger & Ismail 2007).…”
Section: Graham and Driver Datamentioning
confidence: 97%
“…1), and NGC 3384 (Busarello et al 1996, their Fig. 7;Cappellari & Emsellem 2004;Erwin 2004;Meusinger & Ismail 2007).…”
Section: Graham and Driver Datamentioning
confidence: 97%
“…Cortesi et al (2013b) performed a kinematic analysis of the disk and spheroid component separately. The photometric study of Meusinger & Ismail (2007) showed the presence of an "inner component" and and "elongated" component, visible in the PA phot profiles as a local minimum at R = 3" and a local maximum at R = 15". Therefore we considered only the regions at R > 30" in our discussion in section 8.4.…”
Section: Fig B2mentioning
confidence: 99%
“…(e) Mean radius of the last radial bin in units of effective radii. (f) Average value of the photometric position angle and (g) ellipticity ( ), from Krajnović et al (2011) (within 2.5 − 3R e ) and Ho et al (2011) (in the outer regions, where they converge to a constant value) For NGC 3384 and NGC 4564 we used the PA phot from Meusinger & Ismail (2007) and Goudfrooij et al (1994), respectively. (*) Objects for which we used circular radial bins ( = 0) , see section 3.2.…”
Section: Fitting a Rotation Modelmentioning
confidence: 99%
“…The SB0-classification of NGC 3384 indicates the presence of a bar, which can increase ellipticities and should also produce boxy isophotes. There is no evidence for a bar in our data, which exhibit mildly disky behavior throughout, so any bar must be a larger scale feature (Meusinger et al 2007). The B 4 profile of NGC 7457 also does not have the large positive deviations expected of an inner disk.…”
Section: Central Morphologiescontrasting
confidence: 52%